2022
DOI: 10.1038/s41594-022-00724-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for DNA targeting by the Tn7 transposon

Abstract: Tn7 transposable elements are unique for their highly specific, and sometimes programmable, target-site selection mechanisms and precise insertions. All the elements in the Tn7-family utilize a AAA+ adaptor (TnsC) to coordinates target-site selection with transposase activation and prevent insertions at sites already containing a Tn7 element. Due to its multiple functions, TnsC is considered the linchpin in the Tn7 element. Here we present the high-resolution cryo-EM structure of TnsC bound to DNA using a gain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…We found that the transpososome architecture promotes modular association across CAST components, and TnsC has dedicated faces of interaction with TniQ and TnsB, consistent with models of Tn7 transposition 12 , 19 . Cas12k, TniQ and S15 stabilize R-loop formation, but TniQ and TnsC form the primary connection between the CRISPR effector and transposase.…”
Section: Mainsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that the transpososome architecture promotes modular association across CAST components, and TnsC has dedicated faces of interaction with TniQ and TnsB, consistent with models of Tn7 transposition 12 , 19 . Cas12k, TniQ and S15 stabilize R-loop formation, but TniQ and TnsC form the primary connection between the CRISPR effector and transposase.…”
Section: Mainsupporting
confidence: 82%
“…This structure also reveals how Sh CAST transpososome architecture conserves TnsC function across Tn7-like elements. Sh CAST TnsC forms continuous helical filaments on DNA 15 , 18 , which are distinct from TnsC configurations found in the prototypic Tn7 19 and I-F3 CAST subfamily 11 . TnsC from prototypic Tn7 forms heptameric oligomers 19 and led to the original hypothesis that the ring would allow segregated interaction interfaces: the TnsD interface maps to the N-terminal face, and the TnsA–TnsB interface maps to the C-terminal face 19 .…”
Section: Discussionmentioning
confidence: 84%
“… 7 , 20 Altogether, the structure of the Cas12k-transposon recruitment complex establishes a paradigm for CRISPR-transposon systems and other Tn7-like transposons that rely on the interaction between a sequence-specific DNA binding protein and an oligomeric AAA+ ATPase for site-specific transposon insertion. 34 , 35 , 36 ,…”
Section: Discussionmentioning
confidence: 99%
“…TnsA also stimulates synapse formation and therefore should be important for the donor complex formation ( Choi et al, 2013 ). A model of this process has been proposed ( Shen et al, 2022 ). All these considerations point to the fact that, very likely, the TnsA-TnsB complex adopts different conformations from that of the STC.…”
Section: Discussionmentioning
confidence: 99%